The Position of The Validity of Digital Signatures in Internet Sales Transactions: Perspectives of the Civil Code and the Consumer Protection Law - Wulandari, Andi Sri Rezky; Andika Prawira Buana; Tri Abriana Ma'ruf; Ikhtiari, Athifa; Anisah Daeng Tarring (Universitas Negeri Semarang, 2025)
It is known that in general the process of buying and selling transactions requires a physical meeting between the seller and the buyer, as per Article 1457 of the Civil Code. In the context of modern trade, buying and selling can be done face-to-face, without using original signatures and without territorial boundaries by utilizing information technology. Digital signature emerges as a concept that replaces the word “agree” in electronic transactions. Similar to analog signatures, digital signatures also serve to legitimize existing documents. However, currently there is still much debate regarding the recognition, legal force and legal consequences of electronic signatures, especially when disputes arise between the parties involved. The purpose is to determine and analyze the position of the validity of digital signatures in internet sales transactions: the perspective of the Civil Code and the Consumer Protection Law as well as the position of the parties in the internet Sales and Purchase Agreement. This research uses a normative juridical legal research approach. The approach used is legislation (state approach). In this legal research, analytical descriptive specifications are used. The method used is a literature study (Library Research) and qualitative data analysis using primary, secondary and tertiary legal materials which are interpreted in depth. The resume and discussion is that digital signatures are a very appropriate technique used to guarantee the authenticity of documents and avoid the possibility of someone leaking documents. This technique is much more sophisticated and more efficient than manual signatures. Information technology security is then regulated by law by not being an obstacle to technological development, but rather as a counterweight that provides security guarantees to its users. The law is here to provide protection for information technology.